Шанс для влюбленных: роман / Памела Кент - Кент Памела (Цветы любви, 2002)
Экземпляры: ф.1 (2003) / Инвентарный номер: 44934 / Цена: / Сис.шифр: 84(4Вел)-44 / Авт.знак: К 35 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44